Influence of PE-CVD and PE-ALD on defect formation in permeation barrier films on PET and correlation to atomic oxygen fluence. (18th May 2017) - Mitschker, F; Steves, S; Gebhard, M; Rudolph, M; Schücke, L; Kirchheim, D; Jaritz, M; Brochhagen, M; Hoppe, Ch; Dahlmann, R; Böke, M; Benedikt, J; et al.
Abstract: Defects in SiO x, TiO2 and a-Si:H inorganic barrier films on PET are investigated. Visualization is achieved by reactive oxygen etching in capacitively coupled plasma that leads to the undercutting of the barrier films at defect sites, and defect densities are deduced by SEM imaging. Defect formation is analyzed as a function of absolutely quantified steady state atomic oxygen fluence during the deposition of silicon oxide films and the effect of an additional substrate bias is presented. Macro-defect densities as a function of film thickness are tracked. Barrier films with a barrier improvement of one order of magnitude exhibit macro-defect densities below 160 defects mm −2 .